Facebook proliferation in contemporary youth society vis-a-vis the privacy management and user perceived behavior control / Norulhuda Tajuddin ...[et al.] - Tajuddin, Norulhuda; Mat Dangi, Mohamad Ridhuan; Bahsri, Norizzati; Zamakhsari, Zarirah (2014)
Technological advancement nowadays not only comes out with sophisticated and cutting edge products, but it also has change the way human communicates with each other's. The adoption of internet technology in communication has developed a new dimension of virtual world where people can communicates and interacts online using various social networking media as the channel. To date, Facebook is one of the most popular social networking media with millions of users around the globe. It allows people to interact and connect with others crossing the regions, creates profile and sharing information, uploads photos and videos, send message and keep in touch with friends and so on. Teenagers and young adults are the major users of this social networking media. Despites the benefits and versatility, most people are not aware and take for granted about the privacy concern while using Facebook. Sometimes what is posted on Facebook contain many personal information that could be misused by criminals and unscrupulous individuals that targeted the victims. Therefore, Facebook users must be aware and should wisely use this social networking media and avoid themselves from becoming victims to cybercrime. Hence, this paper attempts to investigate the privacy management among the Facebook users. Further, the researchers also tries to examine how the users control themselves when using the Facebook features such as exchange information, sharing photos, comments and so forth. On top of that, this paper will assess the user's behavior and their concern about the privacy management and other security settings in Facebook.